Earlier spring passage of 'Greenlandic' Northern Wheatears Oenanthe o. leucorhoa on the coast of Belgium. Issue 1 (2nd January 2019) - Desaever, Robert; Bairlein, Franz
ABSTRACT: In temperate regions many migratory bird species have advanced their spring arrival to the breeding grounds in recent decades but such changes are much less known among Arctic species. Here we report on long-term changes in the spring passage of 'Greenlandic' Northern Wheatears ( Oenanthe o. leucorhoa ), as revealed by trapping and ringing along the coast of southwestern Belgium. Between 1990 and 2018, these wheatears advanced their average timing of spring passage by 2.9 days for females and by 2.5 days for males. Neither regional weather variables in spring nor the North Atlantic Oscillation Index was found to be correlated with these changes.